OVERVIEW OF EVALUATION OF THE IMPLEMENTATION OF DENGUE HEMORRHAGIC FEVER PREVENTION AND CONTROL PROGRAM IN THE WORK AREA PUSKESMAS TANAH BARU, DEPOK CITY, IN 2021 - Ernyasih; Munaya Fauziah; Andriyani; Yasmin Nurul Janati (Muhammadiyah International Public Health and Medicine Proceeding, 2022)
DHF is a vector-borne disease. This disease is one of the public health problems that invites attention. Based on the results of the study, it was found that the Tanah Baru Health Center area has the highest cases of dengue fever in Depok City, where there are cases every year, but it is still suspected that it has yet to succeed in reducing dengue cases. This study aims to determine an overview of the evaluation of the implementation of dengue disease prevention and control programs in the Tanah Baru Health Center area of Depok City in 2021. This research is qualitative research with a phenomenological approach. This study's informants were seven Depok City regional government health workers and the community. Data collection is sourced from in-depth interviews, observations, and document reviews using source triangulation and triangulation methods for data validation. In the input system, there is still a lack of need for more resources and funds, a no internalized policy SOP. The processing system has carried out activities such as counseling, PSN, and community involvement, but it still needs improvement. The achievements of the output system still need to be achieved, the morbidity rate is still high, and the ABJ figure is 94%. The description of the input system, process system on activities, and output system in implementing dengue prevention and control programs could be better, but there are still technical obstacles. This program needs good supervision and cooperation across programs and related sectors, especially the common, the community, households (families), and dengue disease in the environment.